Palm oil refinery wastes treatment - Chin, K. K.; Wong, K. K. (Elsevier, 1981)
Effluent from the refining of crude palm oil was subjected to physical-chemical and biological treatment. An inclined corrugated parallel plates oil separator spaced at 25 mm was used with hydraulic loading rates ofO.2. 0.5 and I m³ mol_h. 91% oil and grease removal could be achieved at 0.2 m³ m–2 _h. Coagulation and flocculation carried out on batch samples after oil and grease separation revealed that with 100 mg 1- I alum addition BOO was reduced from 3500 to 450 mg 1–1 and COD from 8600 to 750 mg 1–1 after 30 min settling. Higher doses of alum and doses of polyelectrolyte, activated carbon and sodium hypochloride did not yield significant additional reductions in BOD and COD. Batch dissolved air flotation (OAF) removed 90% of the suspended solids with 2.7% solids in the thickened sludge at an A/S ratio of 0.014. This method yielded the similar effluent quality as the inclined corrugated plates oil and grease separator. Field data from a OAF plant compare closely with data achieved in this study. Activated sludge treatment on the effluent from the oil separator yielded a BOD of 46 mg I–1 with a loading rate of OJ g BOD (g MLVSS) –1 day. Total dissolved solids (TDS) remained high and removal through coagulation and chemical oxidation brought the COD level down to around I80mg I–1 Biokinetic coefficients Y. lid' K and K, were found to be 0.S5 g VSS (g BOD) –1. 0.016day–1. 0.12 g BOD (g VSS) –1 <day and 510 mg 1–1 BOD respectively.